Futures of psychiatrists 2020: external and internal challenges - Ikkos, George (Int Psychiatry, 2010)
At the turn of a new decade how might the futures of psychiatrists look? Here we address issues of social inclusion and, also, the professional identity and relationships of psychiatrists.